Novel Compound Heterozygous TMPRSS15 Gene Variants Cause Enterokinase Deficiency - Wang, Lan; Zhang, Dan; Fan, Cheng; Zhou, Xiaoying; Liu, Zhifeng; Zheng, Bixia; Zhu, Li; Jin, Yu (Frontiers in Genetics, 2020)
Background: Enterokinase deficiency (EKD) is a rare autosomal recessively inherited disorder mainly characterized by diarrhoea, hypoproteinaemia and failure to thrive in infancy. Loss-of-function variants in the TMPRSS15 gene cause EKD. Methods: We report the clinical manifestations and molecular basis of EKD in a Chinese child. We investigated in vitro two TMPRSS15 variants: the c.1921G>A as a possible splicing variant by minigene assay; the c.2396T>A(p.Val799Asp) as a missense change by protein expression analysis, enterokinase activity and effect on cellular localization. Results: The proband presented with intractable diarrhoea accompanied by vomiting, failure to thrive and hypoproteinaemia in his second year. Genetic analysis showed that the patient was compound heterozygous for two variants in the TMPRSS15 gene: c.[1921G>A];[2396T>A]. The c.1921 G>A variant may change the glutamic acid 641 into lysine; this change is predicted to be benign by bioinformatics analysis. However, it was predicted to disrupt the splicing donor site. Our minigene assay revealed that c.1921G>A caused the complete skipping of exon 16. The c.2396T>A(p.Val799Asp) change in the serine protease domain predicted to be deleterious hitting an evolutionary conserved amino acid. Functional studies in vitro revealed that the p.Val799Asp variant decreased the total expression level of TMPRSS15 by 29%, and the enterokinase activity of p.Val799Asp mutants was decreased by 37%, compared with that of wildtype. Conclusion: We reported an EKD patient with novel compound heterozygous variations in the TMPRSS15 gene, expanding the genotypic and phenotypic spectrum of EKD. The functional characterization in vitro demonstrated that the c.1921G>A variant alters pre-mRNA splicing and the p.Val799Asp variant leads to a decrease in protein expression and enzyme activity.